Hair-Bearing Expanded Scalp Flap for Total Beard Reconstruction in Patients With Chin and Submental Postburn Scars. Issue 2 (12th March 2023) - Ding, Jianke; Chu, Feifei; Yu, Zhou; Liu, Chaohua; Yang, Qing; Tang, Yinke; Ma, Xianjie
Abstract : Background: Loss of beard in adult male caused by severe burn may cause cosmetic and psychological problems for these patients. Reconstruction of the beard with hair-bearing skin flaps in similar color and texture of the surrounding tissues remains a challenge. Methods: Eight male patients suffered from submental postburn scar and beard loss were treated by using the hair-bearing expanded scalp flap. A 1000 mL nephroid tissue expander was first implanted under the frontal and mid scalp. After a 3 to 4-month tissue expansion, the expanded hair-bearing scalp flap based on bilateral superficial temporal vessels were raised and transferred for beard reconstruction, and the cutaneous pedicles were curled into tubes. Delay and division of the pedicles were performed 3 to 4 weeks after flap transfer. Results: Eight male patients with postburn scar and beard loss were successfully treated with no major complication. One patient suffered from edge necrosis at distal end of the flap and healed after daily dressing change. Chin and submental areas were repaired by expanded scalp flap and total beard was reconstructed at the same time. All donor sites were closed directly without skin grafting. Conclusions: The modified expanded bipedicled scalp flap provides an easy and reliable way for total beard reconstruction and large-scale submental scars repairment.